PERLINDUNGAN HUKUM ATAS HAK KEKAYAAN INTELEKTUAL HASIL PENELITIAN DOSEN - Sardana, Layang; Suryati, Suryati; Disurya, Ramanata (Faculty of Law, University of Palembang, 2020)
Intellectual Property Rights (IPRs) defines as rights about the property arising of human intellectual abilities. The skills may include the field of technology, science, art, and literature. The law must be able to protect the intellectual work so the community can develop their creativity and ultimately leads to the successful goal of protecting IPRs. The aim of this study is to explore the legal protection of IPRs for the Lectures’ research findings. This study applies normative juridical research method that focuses on positive legal norms governing the Legal Protection of IPRs for lecturers’ research findings. The results of this study are (1) a substantive requirement that requires applied patent meets requirements include brand new product, inventive, applicable through the basic provisions of article 2 to 5 of Patent Law, and (2) Based on the existence of copyrighted books, as previously reviewed that the protection system adheres to automatically protection which means in order to obtain legal protection it is not compulsory for the creator to go through the registration process as the protection is existed since the work was created, such as books copyrights.